The relationship of mast cell density in pulmonary, gastric and ovarian malignant epithelial tumors with tumor necrosis and vascularization - Kaya, Şeyhmus; Uçmak, Feyzullah; Bozdağ, Zübeyir; Firat, Uğur (Polish Journal of Pathology, 2020)
Although many studies have been conducted to explore the relationship between mast cells (MC) and angiogenesis, comparison of this relationship with tumor necrosis has not been investigated to the best of our knowledge. Therefore, the relationship between MC and neovascularization in stomach, lung and ovarian malignant epithelial tumors (165 cases) in necrotizing or non-necrotizing cases was explored in this study. We immunohistochemically studied anti-mast cell tryptase antibody for MC and anti-CD34 antibody for vascular structures. MCs in the intra- tumoral and peritumoral fields, as well as vascular structures with luminal and monocellular appearances in the intratumoral field, were counted in each sample. Ten magnification fields were analyzed for each sample. In stomach and lung cases, the non-necrotizing group exhibited a greater number of MC and vascular structures in total. In ovarian cases, more MCs were counted overall in the necrotizing group, but there were fewer vascular structures. The increase in the number of MC and vascular structures in lungs and stomach in the non-necrotizing group supports the theory that MCs are involved in tumor progression. Necrosis, which can be induced on the basis of restricted neovascularization through inhibition of MCs in lung and stomach tumors, may be a treatment method.